Desalination - Yonar, Taner (IntechOpen, 2017)
Increasing population and environmental pollution are the main stress on freshwater sources. On the other hand, freshwater needs of human being increase dramatically every day. From agriculture to industry and from household to recreation, we need freshwater. In the near future, saltwater and brackish water bodies may be the main source of freshwater for our planet. Desalination phenomena are now being implemented with increasing interest. The book on desalination provides a valuable scientific contribution on freshwater production from saltwater sources. In this book, necessary theoretical knowledge and experimental results of different desalination processes are presented.